Kube Devops Framework Algorithm - et. al., Shaily Goyal, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Every business in this age is migrating in the vicinity of the Internet expeditiously. However, to hold on to the customers, holding on to the efficiency of the web services is indispensable as a slow loading website can turn out to customer dissatisfaction. Sometimes customers can be lost due to some seconds or even milliseconds. This research paper targets designing an algorithm for the framework which focuses on the performance optimization of similar web services. This algorithm adds intelligence to the framework by running pre-tests on the docker image to analyse the local response time of the application if it falls under the standard requirements or code optimization is the necessity. The algorithm is responsible for performance tuning and the migration of the application. Besides, it also solves the speed lag issue that can be caused due to network congestion. The algorithm replaces the tedious manual effort of monitoring and optimizing the performance of the application post-deployment, making the proposed framework an asset to draw to customer satisfaction.